Study on virtual computing resource scheduling for network performance optimization - Yu-wei WANG; Min LIU; Bing-yi FANG; Chen-chong QIN; Xiao-long YAN (Tongxin xuebao)
A deep insight into the relationship between vCPU scheduling and I/O transmit in Xen was provided.Then an effective and lightweight recognition method,through which could identify the so-called NSVM (network queuing sensi-tive virtual machine) that was more vulnerable to the congestion in I/O transmit was put forward.Furthermore,a novel mechanism for resource assignment and scheduling called Diff-Scheduler was proposed.It could schedule the vCPU of the NSVM more frequently than other VM in different pools independently.Evaluations based on a prototype of Xen platform featured Diff-Scheduler show that the proposed mechanism significantly improves the network performance of VM.Specifically,comparing with the default mechanism of Xen,Diff-Scheduler proposed jointly enhances throughput,latency remarkably and ensures the fairness of resource allocation at the same time.